2021
DOI: 10.1016/j.jretconser.2020.102281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of auditory sense on trust and brand affect through auditory social interaction and control

Abstract: Voice assistants—or voice-enabled artificial intelligence—have changed the way people interact with their surroundings dramatically. Utilizing an enactive view of social cognition theory, this study demonstrates how voice assistants can act as [semi] autonomous agents to hold instantaneous social interactions with consumers. This research employed two experimental studies. Study 1 used two voice assistant mobile applications, Microsoft Cortana and Google Assistant, and Study 2 used Amazon Alexa and Microsoft C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The first category is focused on the technological attributes of SVAs and explores the effect of their voice, language, security and privacy, etc. (Davenport et al , 2020; Pagani et al , 2019; Poushneh, 2021). The second category analyzes SVAs from the point of view of users, examining their perceptions, motivations, gratifications and behavioral intentions (McLean and Osei-Frimpong, 2019; Shin and Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first category is focused on the technological attributes of SVAs and explores the effect of their voice, language, security and privacy, etc. (Davenport et al , 2020; Pagani et al , 2019; Poushneh, 2021). The second category analyzes SVAs from the point of view of users, examining their perceptions, motivations, gratifications and behavioral intentions (McLean and Osei-Frimpong, 2019; Shin and Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the first category examines what technological attributes of SVAs optimize their employment, focusing on aspects such as voice, language, security and privacy (de Barcelos Silva et al , 2020; Davenport et al , 2020; Poushneh, 2021). In traditional communication, the speaker’s voice and language provide important information about her/him, such as emotions, credibility, reliability and personality factors (Nass et al , 1997; Till and Busler, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When ordering at drive thru window or calling a travel agency, respondents indicated that the use of a human-like voice could set unrealistic expectations about the types of capabilities and interactions available. Other work on perceptions of synthetic voices has noted similar issues (Kühne, Fischer, & Zhou, 2020;Poushneh, 2021). To help address the potential gap between user expectations and the functional capabilities of a highfidelity computer-generated voice, some respondents emphasized the importance of a disclaimer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researchers suggest that brands should develop a suitable personality for their virtual assistants that meet consumers' needs and desires based on brand marketing objectives (Garcia et al, 2018). Poushneh (2020) conducted two studies examining participants' auditory communication with voice assistants. The researcher found that consumers feel in control when interacting with voice activated smart speakers, and this sense of control increases consumers' trust and contentment with the virtual assistant's brand.…”
Section: Virtual Assistants As Opportunities For Advertisersmentioning
confidence: 99%
“…The researcher found that consumers feel in control when interacting with voice activated smart speakers, and this sense of control increases consumers' trust and contentment with the virtual assistant's brand. For example, users interacting with Amazon's Alexa feel in control of the communication experience and therefore have an increase in the level of trust in the overall Amazon brand (Poushneh, 2020). Evidently, virtual assistant devices have provided a variety of benefits for consumers that enable marketers to interact with consumers in unprecedented ways.…”
Section: Virtual Assistants As Opportunities For Advertisersmentioning
confidence: 99%